(untitled) (Research, Society and Development, 2020)
Sorghum is a plant of tropical origin, of short days and with high photosynthetic rates, requiring a warm climate in order to express its production potential. The objective is to evaluate the agroclimatic aptitude of the cultivation of sorghum that allows to visualize or identify its productive potential in the state of Pernambuco. The pluviometric data were acquired from the Northeast Development Superintendence and the Pernambuco water and climate agency, the temperature data were from the National Institute of Meteorology and estimated by the estima_T software between the period 1960-2019. In the region of the high sertão and sertão there is moderate fitness due to excess water. In the agreste region full fitness was obtained with prolonged rainy season. In the Zona da Mata and Litoral regions, fitness is unrestricted. The study was carried out using information from the rainy season and without the aid of irrigation, that is, taking into account the rainfed planting.